Emotional Abuse dalam Hubungan Suami-Istri - Greta Vidya Paramita (Bina Nusantara University, 2012)
In a marriage relationship, generally husband and wife has the commitment to live together and make each other happy. A spouse is expected to be a sparring partner, one who will always be there to share the good and bad times. Unfortunately, this situation doesn’t always happen. One of the factors leading to this unhappiness is the presence of emotional abuse. Emotional abuse is a psychological violence which has the contribution in decreasing the victims self confidence. Article describes various patterns of emotional abuse, characteristic of the abuser, consequences of the abuse, and how to respond to the abuse. There are also some suggestions to prevent or either cope the emotional abuse. The method used in this research is literature study. As a conclusion, emotional abuse in marriage relationship can be prevented by getting to know the partner personalities before the marriage. If emotional abuse occurs in a husband and wife relationship, the victim alone or together with the partner should seek professional help.